MANAJEMEN KURIKULUM DAN PEMBELAJARAN SD SOLIHUDDIN SCHOOL THAILAND - Sari, Noerlita; Triwoelandari, Retno; Fahri, Muhammad (Program Studi PGMI, 2018)
This study aims to examine: (1). Curriculum and learning management, (2). Curriculum planning in the school, (3). Organizing the curriculum in the school, (4). Implementation of the curriculum in the school. This research uses descriptive qualitative research method. Data research were collected through interviews, observations, document studies. Further data are analyzed, reduced, verified then drawn conclusions. The results of this study show that: First, curriculum and learning management at Solihuddin School begins with the planning, organizing, and implementation of the curriculum. Second, Curriculum Planning Solihuddin School has been running with a structured but still needs to be done alignment of plans that have been made in order to be planned all that has been set at planning meetings conducted routinely at the beginning of the semester. Third, the organizing of curriculum at Solihuddin School covers two things: structural and academic. Structurally a curriculum organizing system under the command of the Director (Principal). While the academic organization of the curriculum is developed in the form of an organization that is curriculum based on separate subjects (Saparated Subject Curriculum). Fourth, the implementation of curriculum at Solihuddin School is divided into two levels namely the implementation of school and class curriculum. In the implementation of school-level curricula undertaken by the principal is still less than the maximum because of the lack of existence of the principal. While for the implementation of the class-level curriculum implemented by the teacher is maximal enough with evidence in the learning process has been following the times.